First approximations of historical-critical pedagogy and the CTS approach: Teaching Newton’s 1 st Law (Research, Society and Development, 2020)
This article aims to describe a didactic-pedagogical practice applied to first-year high school classes for understanding Newton's 1st law. For this, a digital resource was used, Google Forms, and all the steps expressed were based on the historical-critical pedagogy and the CTS approach. It was noticed that, with the use of this foundation, the students actively participated in the process of building their knowledge and, because it involved social issues, also provided subsidies for citizen training. Thus, in addition to contributing to his social and academic background, he is presented in a practical way the usefulness of the knowledge developed over the years.